The reasons for increasing employment demand in the public sector in Turkey - Yavuzaslan, Abdulkerim (Studia Mundi – Economica, 2015)
The economic changes taking place in the world and in Turkey, have led to changes in people’s employment demand. Before 2000 government jobs had been considerably less attractive in Turkey, after 2000, when the economic crisis occurred in Turkey public employment demands started to increase. One of the reasons for this that a growing number of people have started to face the unemployment situation that made the formerly less desired public employment more alluring. Beyond employment security there have been also reasons Turkish people choosing to work for government. The goal of this paper how employment demand of Turkish people is changing. Based on last few decade's employment data the paper, will try to shed some light on the reasons behind the related new labor market tendencies.
Keywords: Working Life; Career; Employment